CHINA'S INTERNATIONAL PEACEKEEPING CONTRIBUTIONS AND THE EVOLUTION OF CONTEMPORARY CHINESE STRATEGIC CONSIDERATIONS (The Strategic Review for Southern Africa, 2020)
Following the end of the Cold War and significant changes in the international community, Chinese leaders moved from a reluctant stand in United Nations (UN) activities to a position of active cooperation in UN peacekeeping. In fact, China became the biggest contributor of troops to UN peacekeeping operations among the permanent members of the Security Council. Towards the mid-2000s, China was involved in all seven UN peacekeeping operations on the African continent. This dramatic surge in Chinese peacekeeping participation coincided with Beijing's efforts in the early 2000s to deliberately expand its economic and diplomatic influence globally through trade and diplomatic links, as well as through its participation in international organisations, including UN peacekeeping operations. However, there have always been limits to China's involvement in peacekeeping operations. Beijing's views on peacekeeping have consistently been based on a sound respect for state sovereignty and the principle of non-intervention. In this context, this article points out that on the one hand, China is increasingly expected to concern itself with the global responsibilities of a great power,but as its strategic and material interests have become more integrated and entangled with the African continent, Beijing is more and more compelled to consider its national interest and to protect those interestsin Africa. Consequently, China's growing involvement in peacekeeping has become more difficult to reconcile with the country's commitment to non-interventionism, particularly as witnessed in the case of South Sudan.
Keywords: Cold War; international community; United Nations; cooperation; peacekeeping; China; Security Council.; African continent; Beijing; diplomatic influence; international organisations; state sovereignty; non-interventionism; South Sudan; post-Cold War; France; Britain; foreign policy; non-combat; Mali; Joseph Nye; Soft power; hard power; global norms